Efektivitas Penggunaan Media Magic Study Box dalam Meningkatkan Pemahaman Konsep Siswa pada Pembelajaran IPA Kelas V di MIN 4 Bone - Nursyafika, Nursyafika; Nur, Suriani; Salam, Evelina Satriya (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research aims to determine the effectiveness of the use of magic study box media in increasing students' conceptual understanding in learning science for class V at MIN 4 Bone. The method used in this research is quantitative research with the design used is the One Group Pretest-Posttest Design. In this study, the samples were all students of class V MIN 4 Bone, totaling 17 people. The instrument used in this study was a concept comprehension test in the form of an essay. Then data analysis was carried out using descriptive statistical analysis through the Statistical Package Social Science (SPSS) Version 22 program. The data obtained by the study were analyzed using the SPSS Statistical Version 22 application, in order to be able to find out the results of the calculation of the pretest-posttest descriptive statistical values, hypothesis testing. This research was conducted in class V MIN 4 Bone with 17 students. The results of the study after using the treatment using the magic study box media, showed that the values obtained by students in class V MIN 4 Bone at the time of the posttest increased with an average of 77.35, as well as with the value of each indicator of student understanding of the concept experienced an increase and can be seen from the t-test on pretest and posttest scores, it can be seen that if the value (significance) 2-tailed is 0.000 <0.05 then H0 is rejected and H1 is accepted, which means that the media magic study box is effective in increasing students' understanding of the concepts of class V in MIN 4 Bone, because the significance value obtained is 0.000.